Comparative Analysis of the Influence of Selected Physical Factors on the Level of Pain in the Course of Temporomandibular Joint Disorders. (10th October 2020) - Kopacz, Łukasz; Ciosek, Żaneta; Gronwald, Helena; Skomro, Piotr; Ardan, Roman; Lietz-Kijak, Danuta
Abstract : Introduction . Temporomandibular joints (TMJs) play a very significant function in the activity of the locomotor system of the masticatory system. But they are often a source of pain, myopathy, myoarthropathy, and malfunction of their surrounding or internal structures. The treatment of a patient's discomfort associated with masticatory system dysfunctions strongly depends on their cause. Aim of the Study . The objective of the study was to evaluate the impact of selected physical factors: LED light therapy with electromagnetic field and cryotherapy for the level of pain, in the treatment of patients suffering from temporomandibular disorders (TMDs). Materials and Methods . The study included 60 patients of both genders with diagnosed TMD in a clinical trial. The participants were randomly divided into two groups. Each group consisted of 30 people and was subjected to separate therapies in which LED light therapy with electromagnetic field (MLT) and cryotherapy (CT) were applied. Results . Having assessed the results of the author's own research in terms of analgesic activity, determined on the VAS scale during the daily routine activity of the mandible and its individual movements, in general, each of the studied groups demonstrated a considerable decrease in the level of the patients' perception of pain (<0.001). Having compared both the therapeutic methods used, a greater reduction in the level of perceived pain was achieved with MLT (p = 0.002 ). The type of therapy used turned out to be the only significant factor for the magnitude of this reduction. Conclusions . Conclusions based on the results of our own research indicate that the selected methods of treatment demonstrate an analgesic effect in terms of the overall discomfort in the course of TMD, and that they may be an alternative pain relief thereby reducing the patient's intake of painkillers.